Teknologi Informasi Desa, Upaya Meningkatkan Partisipasi Dan Keterampilan Masyarakat Dalam Pembangunan Desa (Pemanfaatan Limbah Minyak Jelantah Menjadi Karbol) - Fadilla Oktaviana (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2019)
The aim of the Community Service Program, Kuliah Kerja Nyata-Pembelajaran dan Pemberdayaan Kepada Masyarakat (KKN-PPM) is to improve the skills of society, especially housewives. The partners of this activity are non-productive communities in Sindanglaya village, Cinangka. The problem faced does not know the use of used cooking oil/minyak jelantah to produce products that are useful and have selling value. The method of implementing this service is through (1) Survey through observation, interviews, and analysis of problems and potential of the village, (2) Training on making carbolic acid from minyak jelantah, (3) training on making detergent powder. The results of this program are increasing knowledge and skills of the community regarding (1) processing minyak jelantah into carbolic acid, and (2) making powder detergent. This program is expected to facilitate the community in increasing their knowledge and skills in processing used/waste materials into products that are useful and have selling value, therefore that the societies in Sindanglaya become productive communities.